Competence Approach to the Preparation of Teachers of History - Oleksandr Polishchuk (Pedagogical Discourse, 2017)
It is established that at the present stage of development of Ukrainian society the vector of political cooperation has changed, which increased the requirements to professional training of the future teachers, particularly teachers of history, who the most detailed and professionally, using modern innovative technologies, introduce the young man with the past, compares with the present, forms the world outlook. In this regard, they require a high level of intellectual development, civil position, national identity, social competence, active and responsible attitude to life, independence and flexibility of thinking, willingness to the effective explanation of problem situations, ability to continuous personal and professional improvement. Speaking about these components, we realize that they are the components of the competencies that should be taught and that should be developed by the student of pedagogical University.It is proved that with the change of the political situation the person is in the state of splitting, and it is education that can overcome this condition, education with a new vision, new methods and new priorities, that is, people of competence training which focuses not on «knowledge for knowledge», but «knowledge for survival». It is proved that the competence reflects both praxeological and gnoseological side and is understood as the mastering of knowledge, and the ability to flexibly apply it in real life. So, competence is nothing more than a situational category, which is expressed in the willingness to engage in any activity in specific professional situations. According to this it is established that the components of professional competence, which is formed during training in higher educational institution while obtaining a degree a teacher of history. Therefore, the task of higher educational institution in training history teachers involves not only enriching the student’s knowledge of historical facts, events, but also teaching him or her how to compare, evaluate historical processes from the point of view of time, without disturbing their accuracy.Special attention is paid to socio-psychological characteristics of the future teacher. The stages of teachers’ development are revealed. Despite the uncertainties and the stresses in modern society, the learning process in the university requires from the student deep knowledge of the psyche of the pupil, understanding their mental states, ability to select the information, to control their activity and behavior. To do this, the future teachers need cognitive skills that form the intellectual basis of professional competence, which is characterized as a complex personal formation, which optimally combines professionally important knowledge, abilities, skills, motives, value orientations, attitude of the person and determines the person’s ability to self-realization and self-determination in effective pedagogical activity.It is mentioned that each graduate, who obtained qualification of a history teacher should know: the foundations of general-theoretical and professional disciplines to the extent necessary for carrying out scientific research; the latest researches in the field of historical didactics, methodology of teaching and upbringing, ways of teaching in secondary school and work with gifted children; fundamentals of scientific activity; the main directions of development of education, systematization, processing, analysis, generalization and use of information; the foundation of methodological work on the speciality, preparation of informational and scientific-methodological materials; advanced learning technologies and active learning methods; experience in the implementation of humanistic ideas in domestic and foreign pedagogy; psychology of communication with pupils and adults; object, subject of history as a science and its relationships with other components of social studies; basic provisions of philosophical understanding of historical issues; categories of historical science; regularities, genesis, current state and main directions of development of Ukrainian historiography; chronology of the main events of domestic and world history.By the mastery of these competencies the teacher of history can form the worldview of the future patriot of the state, the citizen, who is able to perform relevant tasks, independently to make decisions, to analyze situations and so forth. It is proved that the competence approach in education is associated with the personal oriented and active approaches to learning, as it concerns the identity of the student and can be implemented and tested only in the process of performing by the specific student of the specific set of actions. Key words: competences, pedagogue, pedagogical activity, higher educational institution, subject, world outlook.